Peningkatan pemahaman mahasiswa tentang komunikasi pembangunan melalui edukasi berbasis digital - ., Astin; ., Sriwangi; Kapege, laode Aharuddin; Sanjaya, Aprilia Suci; Merlyns, Rety Reka (CV. ITTC INDONESIA, 2026)
This community service program aims to improve students’ understanding of the concept and practice of development communication through a digital education approach. The program was motivated by the limited ability of students to integrate development communication theory with the effective use of digital media. The activity was conducted at the Faculty of Social and Political Sciences, Halu Oleo University, in September 2025, involving 35 Communication Science students. The implementation consisted of four main stages: preparation, digital education sessions, evaluation, and reflection. The materials were delivered through interactive lectures, group discussions, and hands-on activities in creating digital content on development communication themes. The results showed a significant improvement in students’ understanding, with the average score increasing from 61.2 pre-test to 87.5 post-test. Students also demonstrated creativity in producing digital content such as educational videos, infographics, and social campaign posters on sustainable development issues. Moreover, this activity strengthened students’ digital literacy, communication ethics, and participation in local development issues. The digital education approach proved effective in developing communication competencies that are adaptive to technological advancements and societal needs.